Late Diagnosis of Primary Hyperoxaluria Type 1 After Kidney Transplant - Sobreira, Sabrina Maria Araujo; Neri, Beatriz de Oliveira; Adeodato, Vanessa Gurgel; Dantas, Arthur Holanda; Sobreira Neto, Sebastiao Alves; Teixeira, André Costa; Esmeraldo, Ronaldo de Matos (Brazilian Journal of Transplantation, 2026)
Primary hyperoxaluria type 1 is a rare and often unrecognized cause of renal allograft dysfunction and loss, particularly when renal disease is attributed to recurrent nephrolithiasis. We report the case of a 62-year-old woman with a history of bilateral nephrolithiasis and prolonged use of anti-inflammatory drugs who underwent kidney transplantation with immediate graft function and an initially favorable course. After an extended period of stability, late and progressive graft dysfunction occurred. Allograft biopsy demonstrated tubular injury associated with extensive calcium oxalate crystal deposition, suggesting oxalosis. Serum oxalate was 18.6 µmol/L, and urinary oxalate was 94.9 mg/24 h. Genotyping identified a homozygous pathogenic variant in the AGXT gene, confirming the diagnosis of primary hyperoxaluria type 1. Review of the medical history revealed nephrocalcinosis in native kidneys, and family screening identified a sibling with nephrolithiasis. Pharmacological-dose pyridoxine was initiated as first-line therapy based on the responsive genotype, followed by RNA interference therapy with lumasiran due to the high risk of graft loss, resulting in initial stabilization of graft function. This report emphasizes that primary hyperoxaluria type 1 should be considered in transplant recipients with a history of nephrolithiasis, even in adulthood, and that post-transplant identification has direct implications for graft prognosis, therapeutic approach, and family screening, highlighting the need for metabolic and genetic investigation in selected cases before transplantation.